Application of Chromosome Microarray Analysis for the Differential Diagnosis of Low-grade Renal Cell Carcinoma With Clear Cell and Papillary Features. Issue 2 (February 2020) - Pei, Jianming; Al-Saleem, Tahseen; Uzzo, Robert G.; Dulaimi, Essel; Testa, Joseph R.; Wei, Shuanzeng
Abstract : Clear cell renal cell carcinoma (ccRCC) and papillary renal cell carcinoma (pRCC) are the 2 most common RCCs. However, some RCCs can have both clear cell and papillary features, including clear cell papillary RCC (ccpRCC). They can be a diagnostic challenge in daily practice. Accurate diagnosis of these tumors is important for both patient prognosis and appropriate treatment. Fourteen RCCs with papillary architecture, clear cytoplasm and low Fuhrman grade were analyzed by SNP-based chromosome microarray (CMA). Seven cases had pathologic features of ccpRCC, and all had normal genomic profiles except one that had copy neutral loss of heterozygosity (cnLOH) of chromosome 3 and loss of one copy of the X chromosome. The remaining 7 cases also had papillae and clear cytoplasm. Two of these cases showed losses of chromosome 3 which are typically found in ccRCC. One had a gain of chromosome 7, which is commonly seen in pRCC. The remaining 4 had no alterations of chromosome 3 or 7. However, 3 of these 4 had monosomy 8, which are consistent with RCC with monosomy 8. The remaining case had no copy number alterations. This study shows that low-grade RCC with papillae and clear cell phenotype represents a heterogeneous group, including ccpRCC, ccRCC, pRCC, and RCC with monosomy 8. CMA analysis can be useful for the differential diagnosis of these neoplasms.